Prevalence, risk factors and management approaches for seborrheic dermatitis - Islam, M. Shahidul; Islam, Nahida; Azad Khan, M. Abul Kalam; Hasan, A. H. M.; Rani Saha, Kamana; Happy Moon, Renaissance; Begum, Maksuda; Rubana, Sadia (International Journal of Research in Medical Sciences, 2024)
Background: Seborrheic dermatitis (SD) is a chronic inflammatory condition characterized by immune dysregulation, inflammation and disruption of the skin barrier. Despite its global prevalence, with studies indicating that up to 5% of the population may be affected, the study of the physical and emotional impact of SD on patients is limited. Furthermore, the prevalence of SD appears to be increasing over time. Therefore, this study aimed to determine the prevalence, risk factors and management approaches for seborrheic dermatitis. Methods: This was a prospective study conducted in the Department of Skin and VD, Community Based Medical College Bangladesh, Mymensingh, Bangladesh during the period from June 2020 to June 2022. In our study, we included 150 patients with seborrheic dermatitis who visited the Department of Skin and VD at Community Based Medical College Bangladesh. Results: Among 150 patients, 55% were male and 45% were female. Among all reported patients, 56 (71%) had a moderate level of SD, followed by mild (16%) and severe (13%). Among the HCP (Health care provider) suggested patients, 41% of them had moderate SD, followed by mild (40%) and severe (19%). Out of 150 patients, 50% of them were not allowed to miss their jobs due to the symptoms. Conclusions: The findings of this study highlight the importance of a holistic care approach for managing seborrheic dermatitis. This approach should encompass not only the treatment of the physical signs and symptoms of the disease but also the psychological and social challenges that patients with seborrheic dermatitis face.